Katherine Anne Porter's Ship of fools [videorecording (DVD)] - Kramer, Stanley; Kramer, Stanley; Leigh, Vivien, 1913-1967; Signoret, Simone, 1921-1985; Ferrer, José, 1912-1992; Marvin, Lee; Werner, Oskar, 1922-1984; Ashley, Elizabeth, 1939-; Segal, George; Porter, Katherine Anne, 1890-1980 (Columbia Tristar Home Entertainment, 2003)
In 1933 on a German luxury liner sailing from Mexico to Germany, the separate but interlocking stories of the various passengers begins to unfold. Among the many passengers is a divorcee desperate for love and lost youth, a Spanish noblewoman being deported as a political prisoner, an aging alcoholic ballplayer, and a budding Nazi whose brutishness foreshadows the holocaust to come.